The Livelihood Adjustment of Smallholding Rubber Farming Systems (SRFS) in Southwestern Thailand: Case Study in Ranong, Krabi, Phangnga, and Phuket Provinces - Kongmanee, Chaiya; Somboonsuke, Buncha; Boonkongma, Milinpat; Wettayaprasit, Prawat; Chiarawipa, Rawee; Sae chong, Kamonwan; Thatthong, Kanata; Prapatigul, Panuphan (Forest and Society, 2022)
This study aimed to examine the livelihood adjustment, to analyze factors affecting, and to synthesize the relationships between production and livelihood adjustment in model of SRFS for Ranong, Krabi, Phangnga, and Phuket provinces, in Southwestern Thailand. A sample group of 399 rubber farmers was involved in data collection and 60 key informants were selected as a subsample. A structured interview form and a semi-structured interview form were the tools for data collection. In data analysis, descriptive statistics, linear regression and technical- economic simulation were applied, as well as synthesized model of connections between the production system and livelihood under SRFS was analyzed. The results indicate that rubber farming could be classified into four types: smallholding rubber monoculture farming system (S1) (40.9%), smallholding rubber with fruit tree farming system (S2) (35.8%), smallholding rubber with oil-palm farming system (S3) (49.8%), and smallholding rubber with livestock farming system (S4) (5.9%). These were different in livelihood assets and livelihood outcomes. Smallholding rubber with livestock farming system (S4) was better for livelihood outcomes than the other systems. The social capitals were quite high while the economic capitals were quite low. Livelihood strategies give importance to increasing productivity, reducing costs, financial management, and changes in food consumption. All farms relied on government support and received welfare. For the 10-year economic model (2017- 2026), S4 had the highest margin value. This study synthesized the relationships of production and livelihood adjustment model, showing that the model was composed of four sub-models: production system, support system, strategy, and livelihood adjustment system, and the resulting sustainable livelihood system will be useful for analyzing livelihood adjustments